Faktor-Faktor yang Berhubungan dengan Keluhan Low Back Pain pada Pekerja Penjahit - Elvi Era Liesmayani; Yessy Arisman; Lelly Masnita; Nova SJ; Raihana Azzahra Nasution (Jurnal Bidan Mandiri, 2026)
Background: Sewing work is closely associated with prolonged sitting positions and repetitive movements that increase the risk of musculoskeletal disorders, particularly low back pain (LBP). Objective: This study aimed to analyze factors associated with LBP among sewing workers. Methods: A quantitative study with a cross-sectional design was conducted using total sampling. Data were collected through questionnaires and analyzed using univariate and bivariate analysis. Results: Age, gender, years of service, sitting duration, and working posture were significantly associated with LBP (p < 0.05). Conclusion: Individual and ergonomic factors contribute significantly to the occurrence of LBP among tailors. Ergonomic interventions and proper work-rest schedules are recommended